Q. 5 H3.7( 24 Votes )

# Let us prove:

x^{logy – logz} × y^{logz – logx} × z^{logx – logy} = 1

Answer :

LHS = x^{logy – logz} × y^{logz – logx} × z^{logx – logy}

Now, taking log we have,

Now, RHS = 1

Taking log we have, log 1= 0 =LHS

Therefore, LHS=RHS

Hence, proved.

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Let's Make Logarithm Easy to Understand38 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Let us prove:

log_{10}15(1+log_{15}30) + log_{10}16(1+ log_{4}7)– log_{10}6(log_{6}3+1+ log_{6}7) = 2

If 3 + log_{10}x = 2log_{10}y, then express x by y

Let us prove:

West Bengal Mathematics

Let us prove:

West Bengal Mathematics

Let us prove:

West Bengal Mathematics

Let us prove:

West Bengal Mathematics

Let us prove:

West Bengal Mathematics

If 1 + log_{10}a = 2log_{10}b, then express a by b

If then the value of is

West Bengal MathematicsIf then the value of x is

West Bengal Mathematics